ВОДОРОД ТЕМАСЫН ОҚЫТЫЎДА «ЗИГ-ЗАГ» МЕТОДЫНАН ПАЙДАЛАНЫЎ - Меңлимуратова, З. (FAN va JAMIYAT, 2016)
The article is devoted to the issues of using interactive methods at the lessons in Chemistry on the theme «Hydrogen» using the method «Zig-zag», in particular. The method "Zig-zag" is one of the effective methods used for the student‘s work in small groups. The wide use of handouts in the method "Zig-zag" promotes to the best and fast consolidation of the topic.